If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8y + -1(x + -4x) + 3 = 0 Combine like terms: x + -4x = -3x -8y + -1(-3x) + 3 = 0 Remove parenthesis around (-3x) -8y + -1 * -3x + 3 = 0 Multiply -1 * -3 -8y + 3x + 3 = 0 Reorder the terms: 3 + 3x + -8y = 0 Solving 3 + 3x + -8y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + 3x + -3 + -8y = 0 + -3 Reorder the terms: 3 + -3 + 3x + -8y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 3x + -8y = 0 + -3 3x + -8y = 0 + -3 Combine like terms: 0 + -3 = -3 3x + -8y = -3 Add '8y' to each side of the equation. 3x + -8y + 8y = -3 + 8y Combine like terms: -8y + 8y = 0 3x + 0 = -3 + 8y 3x = -3 + 8y Divide each side by '3'. x = -1 + 2.666666667y Simplifying x = -1 + 2.666666667y
| 3x-150=-39 | | -7(k+3)-4k=-109 | | 3(x-8)=2(x+3) | | 5a-16-8a=-10 | | 4x+1.18=-3.1(2-.01x) | | 2g+3(-8+3G)=1-g | | (-10)=6+4x-6x | | 31-(2c+4)=2(c+6)+c | | 722=485+b | | (5s-2t)-(2s-4t)= | | 7a=36*21 | | X+59+84+X+51=180 | | 128=-8(-2+2p) | | 42p-39=66p-87 | | 7-3d-5=-1+2d-12+d | | 247=-7(-1+8b)-4b | | a+25=-8 | | 3y-x=12 | | 7x+y=12 | | 4(x-4)+5=35-5x | | -14-2x=-4x+26 | | x-3/8=1/8 | | 2x+3=2(x-2) | | 138=n-216 | | 31-(2c+4)=2(c+6)c | | 5(2m+8)=100 | | 5x^2+30x+10=0 | | 16a+37-7a=46 | | 3x^2-3x-44=0 | | 15=2.3b | | 15k+2k=5k+6 | | 1a-4a=2a+1-5a |